DIGITALIZATION OF LOCAL MEDIA AND CHANGING JOURNALISM PRACTICES: A CASE STUDY OF ELAZIG - Yılar, Ömer Enes; Şen, A. Fulya (Mehmet Akif KARA, 2022)
In this study, the digitalization process and changing journalism practices in the local media have been tried to be examined in the case of Elâzığ. At the same time, within the scope of the study, the problems that arise in the digitalization process of the local media were detected, solutions were offered. Within the scope of this research, Sondakika23, which is totally digital, elazigsonhaber.com; operating as news sites of local TV channels, and Kanal23.com were analyzed. Also, news websites of elazigfirat.com and elazighaberkent.com, which operate as internet news sites of local printed newspapers, were analyzed. Finally, social media accounts of these establishments were also examined. Face-to-face interviews were conducted with the managers and editorial staff of the selected media. Using the in-depth interview technique, problems encountered by the local media in the digitalization process were determined and solutions were offered. In addition, the changes that digitalization brought to journalism practices were determined through the interviews. As an example, the news websites of the selected media were analyzed using the Alexa Analysis System. Using the system in question, social media accounts, the number of news items uploaded weekly and the categorical distribution of these items were analyzed. Benefiting from the content analysis method, additional data was provided to the research. As a result of this research, a conclusion below was reached: the local media in Elazig largely adapts to digitalization utilizing the possibilities of new media. However digitalization in this regard has caused a competitive setting. In addition, in this research, some changes in the practices of journalists working in the local media in the province of Elâzığ as a result of digitalization were also determined.

Bu çalışmada yerel medyada dijitalleşme süreci ve değişen gazetecilik pratikleri Elâzığ örneği özelinde incelenmeye çalışılmıştır. Aynı zamanda çalışma kapsamında yerel medyanın dijitalleşme sürecinde ortaya çıkan sorunlar belirlenerek çözüm önerileri sunulmuştur. Araştırma kapsamında, dijital doğumlu olan Sondakika23, yerel televizyon kanallarının haber siteleri olarak faaliyet gösteren elazigsonhaber.com, kanal23.com, yerel basılı gazetelerin internet haber siteleri olarak faaliyet gösteren elazigfirat.com ve elazighaberkent.com haber siteleri ile bu kurumların sosyal medya hesapları incelenmiştir. Araştırma nicel ve nitel olarak iki boyuttan oluşmaktadır. Nitel boyutta örneklem olarak seçilen medya ortamlarının yönetici ve editör kadrosu ile derinlemesine mülakat tekniği kullanılarak yüz yüze görüşmeler yapılmış ve yerel medyanın dijitalleşme sürecinde karşılaştığı problemler belirlenerek bu problemlere çözüm önerileri sunulmuştur. Ayrıca yapılan görüşmelerle dijitalleşmenin gazetecilik pratiklerinde meydana getirdiği değişimler saptanmaya çalışılmıştır. Nicel boyutta ise örnek olarak seçilen medya ortamlarının haber siteleri Alexa analiz sistemi kullanılarak analiz edilerek, sosyal medya ortamları ve haftalık yüklenen haber sayıları ile bu haberlerin kategorik dağılımları içerik analizi yöntemiyle analiz edilmiş ve araştırmaya ek veriler sağlanmıştır. Araştırma sonucunda Elâzığ ilinde yerel medyanın dijitalleşmeye büyük oranda uyum sağladığı, yeni medyanın olanaklarından faydalanıldığı ancak dijitalleşmenin bir rekabet ortamına neden olduğu ortaya koyulmuştur. Ayrıca bu araştırmada dijitalleşme sonucunda Elâzığ ilinde yerel medyada çalışan gazetecilerin pratiklerinde değişiklikler olduğu sonucuna ulaşılmıştır.
YEREL MEDYANIN DİJİTALLEŞMESİ VE DEĞİŞEN GAZETECİLİK PRATİKLERİ: ELÂZIĞ ÖRNEĞİ